Effect of creep-exposure on mechanical properties of Rene' 41 - Gluck, Jeremy V. (Jeremy Victor); Freeman, J. W. (James W.); United States. Air Force. Systems Command. Aeronautical Systems Division; United States. Air Force. Systems Command. Aeronautical Systems Division. Directorate of Materials and Processesd States; University of Michigan. Department of Chemical and Metallurgical Engineering (Wright-Patterson Air Force Base, Ohio : Aeronautical Systems Division, Air Force Systems Command, United States Air Force, 1961)
An investigation of the influence of creep-exposure on the mechanical properties at room temperature of Rene' 41 alloy is in progress. The objestives are to delineate the conditions causing changes in these properties and to develop general principles for predicting the influence of creep on such properties of Ni base superalloys. The results for exposures at 1200 to 1800 F and for 10 to 200 hr show that thermally-induced structural changes reduce room temperature strength and ductility when the exposure temperatures are 1500 F or higher. Limited data indicate that surface reactions also reduce properties with the temperature range of the effect extending to lower temperatures than 1500 F.
"This report was prepared by the University of Michigan, Department of Chemical and Metallurgical and covers work conducted from April 1,1959 to March 31, 1960.
"AD0271480 (from http://www.dtic.mil)."
"August 1961."
Includes bibliographical references (pages 30-31).
Air Force Contract No.
Mode of access: Internet.
Keywords: Materials -- Creep; Crystals -- Structure; Alloys -- Mechanical properties; Alloys